Numerical Simulation of the Flow around a Straight Blade Darrieus Water Turbine - Santiago Laín; Pablo Cortés; Omar Darío López (Energies, 2020)
In this study, three-dimensional transient numerical simulations of the flow around a cross flow water turbine of the type H-Darrieus are performed. The hydrodynamic characteristics and performance of the turbine are investigated by means of a time-accurate unsteady Reynolds-averaged Navier−Stokes (URANS) commercial solver (ANSYS-Fluent v. 19) where the time dependent rotor-stator interaction is described by the sliding mesh approach. The transition shear stress transport turbulence model has been employed to represent the turbulent dynamics of the underlying flow. Computations are validated versus previous experimental work in terms of the turbine efficiency curve showing good agreement between numerical and experimental values. The behavior of the power and force coefficients as a function of turbine angular speed is analyzed. Moreover, visualizations and analyses of the instantaneous vorticity iso-surfaces developing at different blade rotational velocities are presented including a few movies as additional material. Finally, the fluid variables fields are averaged along a turbine revolution and are compared with the steady predictions of simplified steady approaches based on the blade element momentum theory and the double multiple streamtube method (BEM-DMS).